Estimating the Sensitivity and Specificity of Real‐Time Quantitative PCR of Fecal Samples for Diagnosis of Rhodococcus equi Pneumonia in Foals - Shaw, S.D. (J Vet Intern Med, 2015)
BACKGROUND: Real‐time, quantitative PCR (qPCR) methods for detecting Rhodococcus equi in feces have been developed as a noninvasive, rapid diagnostic test for R. equi pneumonia, but have not been evaluated in a large population of foals. OBJECTIVE: The objective of this study was to evaluate the clinical utility of fecal PCR as a diagnostic test for R. equi pneumonia in foals using receiver operating characteristic (ROC) methods. ANIMALS: 186 foals born in 2011 at an R. equi‐endemic ranch in Texas. METHODS: Fecal samples were collected at the time of onset of clinical signs for pneumonic foals (n = 31). Foals with pneumonia were matched by age and birth date to healthy (n = 31) and subclinical (n = 124) control foals; fecal samples were collected from these controls. DNA was extracted from feces using commercial kits and concentration of virulent R. equi in feces was determined by qPCR. RESULTS: Concentration of R. equi in feces differed significantly (P < .05) among groups. The area under the ROC curve for fecal qPCR for diagnosis of R. equi pneumonia was 89% (95% CI, 83–99), with a sensitivity of 94% and specificity of 72%. CONCLUSIONS AND CLINICAL IMPORTANCE: qPCR of feces can be useful as an alternative to tracheobronchial aspiration for the diagnosis of R. equi in foals with clinical signs of pneumonia. Caution should be used in extrapolating results of this study to other populations because fecal concentration of R. equi might vary by geographic location or management practices.